Plant microRNAs as novel immunomodulatory agents - Cavalieri, Duccio; Rizzetto, Lisa; Tocci, Noemi; Rivero, Damariz; Asquini, Elisa; Si-Ammour, Azeddine; Bonechi, Elena; Ballerini, Clara; Viola, Roberto (Scientific reports, 2016)
An increasing body of literature is addressing the immuno-modulating functions of miRNAs which include paracrine signaling via exosome-mediated intercellular miRNA. In view of the recent evidence of intake and bioavailability of dietary miRNAs in humans and animals we explored the immuno-modulating capacity of plant derived miRNAs. Here we show that transfection of synthetic miRNAs or native miRNA-enriched fractions obtained from a wide range of plant species and organs modifies dendritic cells ability to respond to inflammatory agents by limiting T cell proliferation and consequently dampening inflammation. This immuno-modulatory effect appears associated with binding of plant miRNA on TLR3 with ensuing impairment of TRIF signaling. Similarly, in vivo , plant small RNAs reduce the onset of severity of Experimental Autoimmune Encephalomyelities by limiting dendritic cell migration and dampening Th1 and Th17 responses in a Treg-independent manner. Our results indicate a potential for therapeutic use of plant miRNAs in the prevention of chronic-inflammation related diseases.